HCAR2 Modulates the Crosstalk between Mammary Epithelial Cells and Macrophages to Mitigate Staphylococcus aureus Infection in the Mouse Mammary Gland - Xin Ran; Kefei Li; Yutao Li; Weiwei Guo; Xiaoxuan Wang; Wenjin Guo; Bao Yuan; Juxiong Liu; Shoupeng Fu (Advanced Science, 2025)
Abstract Staphylococcus aureus (S. aureus) is a major zoonotic pathogen, with mammary gland infections contributing to mastitis, a condition that poses significant health risks to lactating women and adversely affects the dairy industry. Therefore, understanding the immune mechanisms underlying mammary infections caused by S. aureus is essential for developing targeted therapeutic strategies against mastitis. This study identified hydroxycarboxylic acid receptor 2 (HCAR2) as a potential regulator of S. aureus infection in mammary glands. It is demonstrated that HCAR2 deficiency exacerbates the inflammatory response and disrupts the blood‐milk barrier in the mammary gland during S. aureus infection, with NLRP3 inflammasome‐mediated pyroptosis playing a central role. Activation of HCAR2, on the other hand, suppressed CMPK2 expression, thereby mitigating mitochondrial damage and pyroptosis in mouse mammary epithelial cells (mMECs) induced by S. aureus. Additionally, mitochondrial DNA (mtDNA) released from S. aureus‐infected mMECs activates the cGAS/STING signaling pathway in macrophages, impairing their bactericidal activity. In conclusion, this study highlights the critical role of HCAR2 in S. aureus infection of the mammary gland and provides a theoretical basis for identifying potential therapeutic targets for such infections.